Polynomials: The Remainder and Factor Theorems

1 / 4

# Polynomials: The Remainder and Factor Theorems - PowerPoint PPT Presentation

= remainder = P (- 2) . Polynomials: The Remainder and Factor Theorems. The remainder theorem states that if a polynomial, P ( x ), is divided by x – c, then the remainder equals P ( c ).

I am the owner, or an agent authorized to act on behalf of the owner, of the copyrighted work described.

## PowerPoint Slideshow about 'Polynomials: The Remainder and Factor Theorems' - ross

Download Policy: Content on the Website is provided to you AS IS for your information and personal use and may not be sold / licensed / shared on other websites without getting consent from its author.While downloading, if for some reason you are not able to download a presentation, the publisher may have deleted the file from their server.

- - - - - - - - - - - - - - - - - - - - - - - - - - E N D - - - - - - - - - - - - - - - - - - - - - - - - - -
Presentation Transcript

= remainder = P(- 2)

Polynomials: The Remainder and Factor Theorems

The remainder theorem states that if a polynomial, P(x), is divided by x – c, then the remainder equals P(c).

Example 1: For the polynomial, P(x) = 2x3 – 8x2 + 45, (a) find P(- 2) by direct evaluation, (b) find P(- 2) using the remainder theorem.

(a) P(- 2) = 2(- 2)3 – 8(- 2)2 + 45

= - 3

(b) Here c = - 2, so divide (synthetically) P(x) by x + 2.

2 - 8 0 45

- 4 24 - 48

- 2 | 2 - 12 24 - 3

Polynomials: The Remainder and Factor Theorems

The factor theorem states that for a polynomial, P(x), if x – c is a factor, then P(c) = 0. Also, if P(c) = 0, then x – c is a factor.

Example 2: For the polynomial, P(x) = 2x3 – x2 + 3x – 4,

use the factor theorem to show that x – 1 is a

factor.

P(1) = 2(1)3 – (1)2 + 3(1) – 4

= 0.

Since P(1) = 0, x– 1 is a factor.

Slide 2

Polynomials: The Remainder and Factor Theorems

Try: For the polynomial, P(x) = x3 – x2 + x – 6,

(a) find P(5) using the remainder theorem, (b) use the factor theorem to show that x – 2 is a factor.

(a) 1 - 1 1 - 6

5 20 105

5 | 1 4 21 99

= P(5)

(b) P(2) = (2)3 – (2)2 + (2) – 6 = 0

Since P(2) = 0, x– 2 is a factor.

Slide 3

Polynomials: The Remainder and Factor Theorems

END OF PRESENTATION

Click to rerun the slideshow.